Higher education issues: an eye on academic mobility : educational and methodological manual for 4th year students (educational and professional program “English language and literature and translation and second foreign language”) - Matiukhina, Yuliia; Shpak, Olena; Матюхіна, Юлія Володимирівна; Шпак, Олена Владиславівна (Kharkiv : V. N. Karazin Kharkiv National University, 2025)
Educational and methodological manual for oral practice on the topic "Higher Education Issues: an Eye on Academic mobility" for 4th-year students of the School of Foreign Languages (educational and professional program "English Language and Literature and Translation and Second Foreign Language") highlights the issue of student mobility and offers modern authentic material on this topic for study, which will allow students not only to strengthen their knowledge in the use of English, but also to improve their communication skills. The manual is advisable to use both during classroom and distance learning, as well as in independent work.

Навчально-методичний посібник з усної практики за темою «Проблеми вищої освіти: погляд на академічну мобільність» для студентів 4 курсу факультету іноземних мов (освітньо-професійна програма «Англійська мова та література і переклад та друга іноземна мова») висвітлює питання студентської мобільності та пропонує до опрацювання сучасний автентичний матеріал з даної тематики, що дозволить студентам не тільки зміцнити знання у використанні англійської мови, а ще й покращити свої комунікативні навички. Посібник доцільно використовувати як під час аудиторної, так і дистанційної форми навчання, а також у самостійній роботі.
Питання вищої освіти: погляд на академічну мобільність : навчально-методичний посібник з усної практики для студентів IV курсу факультету іноземних мов (освітньо-професійна програма «Англійська мова та література і переклад та друга іноземна мова»)
Навчальне видання
Keywords: SOCIAL SCIENCES::Social sciences::Education; knowledge; language; skills; authentic; communicative; oral practice; знання; мова; навички; автентичний; комунікативний; усна практика